Assessment of adaptability and fruit quality in new apple cultivars for intensive orchards - N. G. Krasova; Z. E. Ozherelieva; A. M. Galasheva; M. A. Makarkina; M. V. Lupin (Труды по прикладной ботанике, генетике и селекции)
Background. Competitive early-fruiting apple cultivars with high commercial and consumer qualities, resistant to unfavorable stressors, are required for successful horticulture development.Materials and methods. The study included apple cultivars developed by innovative methods using scab resistance donors (Rvi6) and diploid gamete donors. Foreign cultivars commercialized in the region were also used. Conventional variety testing techniques were applied. Fifteen cultivars released by the Institute of Fruit Crop Breeding (VNIISPK), 6 foreign cultivars, and one reference (‘Antonovka obyknovennaya’) were assessed.Results. Simulating damaging factors helped to identify good resistance of tissues and buds of domestically bred apple cultivars to early winter frosts. These cultivars survived a temperature decrease to –30°C without damage in early winter and without significant damage (no more than 2.0 pts) at –40°C in midwinter, including the scab-immune (Rvi6) cultivars ‘Ivanovskoye’ and ‘Pamyat Hitrovo’, and immune triploids (3×) ‘Aleksandr Boyko’, ‘Akademik Saveliev’ and ‘Vavilovskoye’. Bud damage in ‘Gala’ and ‘Ligol’ was stronger (2.5 pts) and increased to 3.0 pts under simulated temperatures down to –38°C and –40°C. ‘Gala’ showed the lowest resistance in midwinter. Early-fruiting cvs. ‘Blagodat’, ‘Ivanovskoye’, ‘Pamyat Hitrovo’ and ‘Rozhdestvenskoye’ were identified. On average, triploids ‘Blagodat’ and ‘Patriot’, scab-immune ‘Afrodita’, ‘Ivanovskoye’ and ‘Start’, and scab-immune triploid ‘Rozhdestvenskoye’ significantly exceeded ‘Antonovka’ and other cultivars in yield. Conclusion. The new innovative winter cultivars developed at VNIISPK matched foreign cultivars in marketability and consumer qualities, while in scab resistance and adaptability they significantly exceeded most of them. ‘Akademik Saveliev’, ‘Aleksandr Boyko’, ‘Afrodita’, ‘Vavilovskoye’, ‘Ivanovskoye’, ‘Prazdnichnoye’ and ‘Rozhdestvenskoye’ were recommended for intensive-type orchards.